Drugs analysis and citizens safety. Workflows for chemical analysis and structural elucidation of new psychoactive substances in the EU. (May 2021) - Tsochatzis, E.D.; Giannopoulos, G.; Lopes, J. Alberto; Guillou, C.
Abstract: NPS are novel synthesized compounds that are being produced by a slight alteration/modification in the chemical structure of existing illegal substances, already registered in the European Union (EU). A number of products imported from non-EU countries, which have not been necessarily controlled under international law, may be subject to monitoring in agreement with EU legislation. In order to proper establish the chemical identity of seized substances, there is a need to use specific analytical workflows. The latter, many times not available in normal control laboratories, involve the use of powerful instrumentation such as 1 H and 13 C nuclear magnetic resonance (NMR), high-resolution tandem mass-spectrometry (HR-MS), UV/IR and Raman spectroscopy. The time needed for detailed analysis and interpretation of the results demands considerable commitment. A way to maximize this analysis is to employ modern chemoinformatic platforms, which can promote the management and centralisation of analytical data from multiple techniques and instruments, as well as combining tentative identifications with predicted chemical and structural information. The paper presents and discusses existing workflows for monitoring, communication and management of analytical data regarding the structural elucidation and chemical identification of NPS seized in EU by member states customs services, which are of high importance for the safety and security of citizens. The dissemination of all the received information between control authorities strives to help and protect EU citizens by harmful substances. In addition the paper provides an interesting link between safety and security by indicating ways to extend the proposed methodology.